2012
DOI: 10.3109/00016357.2012.741701
|View full text |Cite
|
Sign up to set email alerts
|

Instant dentin hypersensitivity relief of a single topical application of an in-office desensitizing paste containing 8% arginine and calcium carbonate: A split-mouth, randomized-controlled study

Abstract: The tested in-office desensitizing paste containing 8.0% arginine and calcium carbonate provides significantly greater hypersensitivity relief compared to calcium carbonate alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…The formulation derived from this combination, Pro-Argin, has been described as a novel occlusion technology based on the fact that 8% arginine and calcium carbonate are believed to seal exposed dentinal tubules with a plug that contains arginine, calcium carbonate and phosphate thereby providing relief for DH [52]. This claim has been supported by the results of studies which demonstrated relief of DH for variable periods following the use of Pro-Argin mouthwash or paste [52,53]. Although previous systematic reviews have recommended arginine-containing toothpastes for treatment of DH [50,51].…”
Section: Recent Developments In the Treatment Of Dentine Hypersensitisupporting
confidence: 62%
“…The formulation derived from this combination, Pro-Argin, has been described as a novel occlusion technology based on the fact that 8% arginine and calcium carbonate are believed to seal exposed dentinal tubules with a plug that contains arginine, calcium carbonate and phosphate thereby providing relief for DH [52]. This claim has been supported by the results of studies which demonstrated relief of DH for variable periods following the use of Pro-Argin mouthwash or paste [52,53]. Although previous systematic reviews have recommended arginine-containing toothpastes for treatment of DH [50,51].…”
Section: Recent Developments In the Treatment Of Dentine Hypersensitisupporting
confidence: 62%
“…In a 12-week, randomized, double-blind, splitmouth design clinical trial, the in-office application of arginine-calcium carbonate paste provided significant reduction in sensitivity compared with that of the calcium carbonate control, lasting during the entire follow-up period. 18 In addition, in a randomized double-blind active control clinical trial, in-office treatment with arginine-calcium carbonate paste resulted in a significant reduction in sensitivity compared with sodium fluoride gel, which persisted during the 28 day follow-up period. Using scanning electron microscopy, studies also showed significantly better occlusion of tubules after arginine-calcium carbonate treatment compared with treatment with sodium fluoride gel.…”
Section: Laser and Argmentioning
confidence: 99%
“…The development of a therapy that can provide both immediate relief following professional application and a lasting desensitizing effect for a significant time period after use would be of great assistance to clinicians in dealing with DH. 17,18 The results of the present study demonstrate comparable clinical effectiveness for the two dentifrices with significant reductions in measures of tooth sensitivity, observed across all measures, at all predefined time points, i.e., groups I and II respectively, vs baseline. This is in agreement with the studies by Salian et al, 19 Sharma et al, 20 West et al, 21 and Litkowski and Greenspan.…”
Section: Discussionmentioning
confidence: 55%